2016
DOI: 10.1002/htj.21246
|View full text |Cite
|
Sign up to set email alerts
|

CFD Analysis of Steady Laminar Natural Convection Heat Transfer from a Pin Finned Isothermal Vertical Plate

Abstract: Heat transfer behavior with both the conductive and nonconductive fins have been analyzed by examining variations of the local and average Nusselt numbers in two-dimensional flow. The main objective of this study is to quantify and compare the natural convection heat transfer enhancement of fin array with different fin aspect ratio and at different angles of inclination. It is found that significant heat transfer augmentation is obtained for both conductive and nonconductive fins. For conductive fins 20% highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Sahoo et al [17][18][19] employed computational fluid dynamics techniques to analyze heat transfer from pin-finned horizontal and vertical plates. Baqir et al [20] carried out the performance evaluation of improved metal stove over traditional mud chulha.…”
Section: Introductionmentioning
confidence: 99%
“…Sahoo et al [17][18][19] employed computational fluid dynamics techniques to analyze heat transfer from pin-finned horizontal and vertical plates. Baqir et al [20] carried out the performance evaluation of improved metal stove over traditional mud chulha.…”
Section: Introductionmentioning
confidence: 99%
“…They used five different turbulence models and calculated the mean Nusselt number. Sahoo et al 8 analyzed the steady-state laminar natural convection; heat transfer from an isothermal upward extended surface plate. They found that with an increasing number of fins the Nusselt number reduces for laminar heat treatment.…”
Section: Introductionmentioning
confidence: 99%